Frequency, spatial distribution, and genetic diversity of Blastocystis among referred individuals to a clinical laboratory: First report of subtype 9 in Brazil - Bertozzo, Thainá Valente [UNESP]; David, Érica Boarato; Oliveira-Arbex, Ana Paula; Victória, Cassiano [UNESP]; Guimarães, Semíramis [UNESP] (Elsevier, 2022)
The enteric protist Blastocystis has a worldwide distribution, however its prevalence in the human population is still underestimated, especially in developing countries where proper diagnosis is not performed in the routine of clinical laboratories. In this study, we aimed to assess the frequency, genetic diversity, and spatial distribution of Blastocystis isolates detected in fecal samples referred to a clinical laboratory for routine examination in inner São Paulo State, Brazil. A total of 348 leftover stool samples available for disposal from female and male individuals with age ranging from 3 months to 88 years were analyzed by both microscopic examination and PCR/sequencing of the SSU rRNA gene. The overall frequency of Blastocystis sp. was 31% (108/348), including 20.1% (70/348) and 31% (108/348) by microscopic examination and PCR/sequencing, respectively. Significant association was found only between Blastocystis infection and age, since the highest rate of positive samples was detected among 5–9 years old individuals (p < 0.0001). In addition, spatial distribution revealed a wide distribution of the positive samples, however they were densely concentrated in more populated areas. Seven subtypes were identified, namely ST1 (40.7%), ST2 (9.2%), ST3 (45.3%), ST4 (0.9%), ST6 (1.8%), ST7 (0.9%) and ST9 (0.9%). The intra-subtype analysis revealed a total of 25 different alleles previously reported. Here, the findings lead us to highlight the following aspects: (1) the identification of a ST9 isolate is a relevant finding since it is considered a very rare subtype in human infections as well as this is the first report in Brazil; (2) the high frequency of Blastocystis in fecal samples submitted for examination in a clinical laboratory points to the need to consider its search in routine parasitological examinations, (3) the spatial distribution of Blastocystis infection was not homogeneous but concentrated in more populated areas where the access for population to diagnostic services in healthcare is likely to be easier and, (4) the genetic variability of Blastocystis isolates suggests exposure of inhabitants living in inner municipalities to different sources of contamination involving anthroponotic and zoonotic transmission pathways.
Keywords: Blastocystis sp; Clinical laboratory; Frequency; Spatial analysis; Subtypes